A simple and rapid protocol for the genetic transformation of Ensete ventricosum - Matheka, J.; Tripathi, J.N.; Merga, I.; Gebre, E.; Tripathi, L. (Springer, 2019)
Enset (Ensete ventricosum), also known as Ethiopian banana, is a food security crop for more than 20 million people in Ethiopia. As conventional breeding of enset is very challenging, genetic engineering is an alternative option to introduce important traits such as enhanced disease resistance and nutritional value. Genetic transformation and subsequent regeneration of transgenic enset has never been reported mainly due to challenges in developing transformation protocols for this tropical species. Agrobacterium-mediated transformation could be a practical tool for the genetic improvement of enset. However, the efficiency of the transformation system depends on several parameters such as plant regeneration, genotype, explant, selection agent and Agrobacterium strains. As a first step towards the development of transgenic enset, a simple and rapid plant regeneration system was developed using multiple buds as explants. Induction and proliferation of multiple buds from shoot tip explants was achieved on Murashige and Skoog (MS) medium supplemented with 5 and 10 mg/l of 6-benzylaminopurine (BAP), respectively. Shoots were regenerated from multiple buds on MS media containing 2 mg/l BAP and 0.2% activated charcoal. Based on the optimized regeneration protocol, an Agrobacterium-mediated transformation method was developed using multiple buds as explants and the binary plasmid pCAMBIA2300-GFP containing the green florescent protein (gfp) reporter gene and neomycin phosphotransferase II (nptII) selection marker gene. Transgenic plantlets were obtained within 4 months at a frequency of about 1.25%. The transgenic lines were validated by PCR analysis using primers specific to the nptII gene. To obtain uniformly transformed plantlets, chimerism was diluted by subculturing and regenerating the transgenic shoots on a selective medium containing kanamycin (150 mg/l) for five cycles. The uniformity of the transgenic plants was confirmed by Southern blot hybridization and RT-PCR analyses on different tissues such as leaf, pseudostem and root of same transgenic plant. In the present study, we report a simple Agrobacterium-mediated transformation system for generating transgenic events of enset. To the best of our knowledge, this is the first report on the stable transformation and regeneration of transgenic events of enset. The transformation system established in this study can be used for the generation of transgenic enset with important traits such as disease resistance.